Short Communication: Analysis of rhizome color and phytochemical content of 10 accessions of Curcuma zanthorrhiza Roxb. in Jambi, Indonesia - MINARNI MINARNI; RAYANDRA ASYHAR; DARA JULIANA; YOSHUA SHANDY YUDHA; WARAS NURCHOLIS (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Minarni M, Asyhar R, Juliana D, Yudha YS, Nurcholis W. 2023. Short Communication: Analysis of rhizome color and phytochemical content of 10 accessions of Curcuma zanthorrhiza Roxb. in Jambi, Indonesia. Biodiversitas 24: 149-155. Plants are a source of secondary metabolites that have various biological functions and are beneficial for humans, particularly in the health sector. One such beneficial herbal plant, temulawak (Curcuma zanthorrhiza Roxb.), a member of the genus Curcuma L. in the Zingiberaceae family, is widely known as Javanese turmeric. C. zanthorrhiza is a potential source of drugs in the field of pharmacology. One part of temulawak that has an important role is the rhizome, commonly used in the formulation of traditional herbal medicines. There are many pharmacologically active components contained in the C. zanthorrhiza rhizome. Thus, this plant, found in many parts of Indonesia, such as Jambi and Sumatra, is worthy of detailed pharmacological investigation. The study reported in this paper aimed to determine the potential content of secondary metabolites of alkaloids, flavonoids, saponins, tannins/phenolics, and triterpenoids/steroids in 10 accessions of temulawak rhizomes in Jambi. The phytochemical content analysis in temulawak was carried out by qualitative phytochemical screening using dye reagents. Multivariate cluster analysis was carried out to determine the relationships between the 10 accessions based on similarities in the color and phytochemical content of their rhizomes. Generally, the screening results showed that the rhizomes of the 10 C. zanthorrhiza accessions contained the same intensities of alkaloids (dragendof, mayer and wagner), flavonoids, tannins/phenolics (+++) and steroid compounds (++). On the other hand, saponin and triterpenoid were not detected in the tests of rhizomes of the 10 accessions (-). The clustering analysis of the results divided the 10 local temulawak accessions into three clusters. Cluster-1 consisted of two accessions (JM and JBB), cluster-2 consisted of three accessions (JT, JPB, and JBS), and cluster-3 consisted of five accessions (JSS, JJ, JB, JBE, and JG).